THE INFLUENCE OF PHYSICAL WORK ENVIRONMENT, WORK DISCIPLINE, AND AFFECTIVE COMMITMENT ON EMPLOYEES' WORK SPIRIT AT CV. MULYA PRATAMA YOGYAKARTA - Refiana, Erma; Prayekti, Prayekti; Hadi, Syamsul (International Conference on Humanity Education and Society (ICHES), 2024)
Work enthusiasm is doing work more actively so that work can be expected to be faster and better. This research aims to examine and analyze the influence of the physical work environment, work discipline, and affective commitment on employee morale at CV. Mulya Pratama Yogyajarta. The population and sample used in this research were all employees at CV. Mulya Pratama Yogyakarta, totaling 60 people, used nonprobability sampling, more precisely saturated sampling. This research method is quantitative by collecting data using a questionnaire. Data analysis used SPSS Version 25. The results showed that the Physical Work Environment, Work Discipline, and Affective Commitment had a positive and significant effect on Employee Work Morale.